LEGAL PROTECTION OF JOINT MARITAL PROPERTY IN ASSET SEIZURE CASES OF CORRUPTION: AN ANALYSIS BASED ON LAW NUMBER 1 OF 1974 ON MARRIAGE - Taufik, Elsa Mauli (Tanjungpura Acta Borneo Journal, 2025)
Abstract The study examines legal protection of joint marital property in cases of asset seizure resulting from criminal acts of corruption. It is grounded in Law No. 1 of 1974 on Marriage and Law No. 31 of 1999 on the Eradication of Corruption. The research is driven by the growing number of corruption cases in Indonesia, which often lead to asset seizures—including joint property—potentially affecting family economic stability and creating internal conflict between spouses.The study employs a normative juridical method, analyzing statutory regulations and legal doctrines related to the protection of joint marital property. The findings indicate that although law enforcement authorities have the power to seize joint assets suspected of originating from criminal acts, it is essential to safeguard the rights of an uninvolved spouse. This can be achieved through court objection mechanisms and the establishment of a legitimate prenuptial or postnuptial property separation agreement registered with the relevant authorities. Such mechanisms can help ensure that the economic rights of innocent parties remain protected and that seizures are limited only to assets directly linked to the criminal act. Abstrak Penelitian ini mengkaji perlindungan hukum terhadap harta bersama dalam kasus penyitaan akibat tindak pidana korupsi dengan berlandaskan pada Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan serta Undang-Undang Nomor 31 Tahun 1999 tentang Pemberantasan Tindak Pidana Korupsi. Kajiannya didorong oleh meningkatnya kasus korupsi di Indonesia yang berimplikasi pada penyitaan aset, termasuk harta bersama yang dapat berdampak pada stabilitas ekonomi keluarga dan menimbulkan konflik internal pasangan suami istri. Metode penelitian yang digunakan adalah yuridis normatif dengan analisis peraturan perundang-undangan dan doktrin hukum terkait perlindungan harta bersama. Hasil penelitian menunjukkan bahwa meskipun aparat penegak hukum berwenang melakukan penyitaan terhadap harta bersama yang diduga berasal dari tindak pidana, penting untuk memperhatikan perlindungan hak pasangan yang tidak terlibat melalui mekanisme keberatan di pengadilan serta pembuatan perjanjian pisah harta yang sah dan didaftarkan di instansi berwenang. Mekanisme tersebut dapat menjadi solusi agar hak ekonomi pihak yang tidak bersalah tetap terjaga dan penyitaan hanya dilakukan pada aset yang relevan dengan tindak pidana.